TRANSLATION STUDY OF THE FEATURES OF MANIFESTATION OF ANXIETY IN PRESCHOOL CHILDREN - Abduxakimova Sevara Sherali qizi (Modern American Journals, 2025)
This master's thesis investigates the psychological features of anxiety, the causes of its occurrence and forms of appearance in preschool children. The study involved young school-age children. On the basis of the methods "Zina", "Family" and "Determining the level of anxiety", the emotional state of the child, the influence of the family environment and the degree of anxiety were determined. Based on the results of the study, practical recommendations for reducing anxiety have been developed.
Keywords: preschool age, anxiety, psychological analysis, diagnosis, methodology, family environment